Acetylcholinesterase Inhibitory and Antioxidant Activity of the Compounds Isolated from Vanda roxburghii. (28th March 2021) - Ahammed, Salim; Afrin, Rejina; Uddin, Nasim; Al-Amin, Yusuf; Hasan, Kamrul; Haque, Uzzal; Islam, K. M. Monirul; Alam, A. H. M. K.; Tanaka, Toshihisa; Sadik, Golam
Abstract : Vanda roxburghii has been used in traditional medicine to treat nervous system disorders including Alzheimer's disease (AD). We reported earlier a high acetylcholinesterase inhibitory and antioxidant activity in the chloroform fraction of this plant. Therefore, this study was designed to explore the compounds with acetylcholinesterase inhibitory and antioxidant activities from the chloroform fraction of Vanda roxburghii . Phytochemical investigation led to the isolation for the first time of a fatty acid ester: methyl linoleate (1), and three phenolics: syringaldehyde (2), vanillin (3), and dihydroconiferyl dihydro- p -coumarate (4) along with the previously reported compound gigantol (5). Among the isolates, vanillin (3) and dihydroconiferyl dihydro- p -coumarate (4) were found to significantly inhibit the activity of acetylcholinesterase, scavenge the free radicals, exhibit the reducing power and total antioxidant activity, and effectively reduce the peroxidation of lipid. Gigantol (5) and syringaldehyde (2), despite lacking the activity against acetylcholinesterase, exhibited antioxidant activity. Among the compounds, gigantol (5) appeared to be the most potent antioxidant. These findings revealed that V. roxburghii contained compounds with potential acetylcholinesterase inhibitory and antioxidant activity, which support its traditional use in the treatment of AD.